Decomposition of formic acid via carboxyl mechanism on the graphene nanosheet decorated by Cr, Mn, Fe, Co, Ni, Pd, Ag, and Cd metals: A DFT study. (5th January 2023) - Gharib, Azar; Arab, Ali
Abstract: The carboxyl mechanism of formic acid decomposition was investigated on the graphene nanosheet decorated with 8 single metal atoms from the thermodynamics and kinetics point of view using DFT computations. The thermodynamic results showed that for all metal-doped graphene surfaces, the adsorption of studied entities in the gas phase was more favorable compared to the solution phase. The Mn-doped graphene surface was more suitable for the adsorption of studied entities than the other surfaces. Adsorption of CO as a poisoning entity was also more favored on Mn-doped graphene with the highest adsorption energy of −47.56 kJ/mol while the Pd and Co samples were less poisoned with CO intermediate. Our kinetic studies demonstrated that the C–H bond activation was the rate-determining step of formic acid decomposition for all of the examined systems in the gas and solution phases. Additionally, formic acid decomposition was kinetically more suitable on the Mn-doped graphene nanosheet with the lowest activation energy of 73.19 kJ/mol. Graphical abstract: Image 1 Highlights: Adsorption of studied entities in the gas phase was more favorable compared to the solution phase. The Mn-doped graphene surface was more suitable for the adsorption of studied entities. C–H bond activation was the rate-determining step of formic acid decomposition. Formic acid decomposition was kinetically more suitable on the Mn-doped graphene nanosheet.